DIGILANG: ENHANCING ENGLISH PROFICIENCY IN COMMUNITY-BASES TOURISM THROUGH TAILORED E-LEARNING - Nuraeni, Nuraeni; Pratama, Erik Yuda; Afrianto, Yugo (English Review: Journal of English Education, 2023)
This study presents DigiLang, a customized e-learning platform, specifically developed to enhance English for Tourism proficiency among Community-based tourism members in Bogor Regency. The DigiLang platform was tailored to meet the specific purposes of language needs in the tourism sector. Through a comprehensive needs assessment, DigiLang provides a variety of focused resources, including personalized content, interactive modules, and practical exercises designed to foster proficient communication in the context of tourism. Further, the participants involved in this study were 30 villagers from three community-based tourism members who were randomly chosen from three tourism sites located in Bogor Regency. The participants were actively engaged in using DigiLang for English language learning within the tourism context. Their experiences and feedback were collected and analyzed to evaluate the effectiveness and suitability of the DigiLang materials in enhancing community-based tourism members' English proficiency. The results of the survey reveal learners’ positive attitudes towards (1) the user interface, (2) the language content and learning material, (3) the localized learning material. Participants also noted effective ways of online learning using DigiLang platform. Drawing from the outcomes of this developmental research, the DigiLang platform fulfilled the criteria for its adoption as a medium for online language learning, particularly in the English for Tourism context.   s